2004
DOI: 10.1111/j.1349-7006.2004.tb02195.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of BRCA1 and BRCA2 as regulators of DNA repair, transcription, and cell cycle in response to DNA damage

Abstract: pproximately 5% of breast cancers show a familial pattern of occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
397
0
19

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(435 citation statements)
references
References 57 publications
2
397
0
19
Order By: Relevance
“…Our studies have demonstrated that alcohol increases Brf1 expression and Pol III gene transcription to facilitate cell transformation and tumor formation (Zhang et al ., 2013; Zhong et al ., 2011, 2016). BRCA1 is a tumor suppressor (Duncan et al ., 1998; Yoshida and Miki, 2004), which is responsible for repairing damaged DNA (Chen et al ., 2011). Women with an abnormal BRCA1 gene have up to an 80% higher risk of developing breast cancer (Friendenson, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have demonstrated that alcohol increases Brf1 expression and Pol III gene transcription to facilitate cell transformation and tumor formation (Zhang et al ., 2013; Zhong et al ., 2011, 2016). BRCA1 is a tumor suppressor (Duncan et al ., 1998; Yoshida and Miki, 2004), which is responsible for repairing damaged DNA (Chen et al ., 2011). Women with an abnormal BRCA1 gene have up to an 80% higher risk of developing breast cancer (Friendenson, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the encoded BRCA2 protein is involved in DNA repair, transcription, and cell cycle control (Davies et al, 2001;Venkitaraman, 2002;Powell et al, 2003;Yoshida and Miki, 2004). BRCA2 interacts directly with RAD51, which is an essential protein for error-free double-strand DNA break repair by homologous recombination (Sharan et al, 1997;Wong et al, 1997;Xia et al, 2001;Pellegrini et al, 2002;Venkitaraman, 2002;Jackson, 2002;Powell et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…BRCA2 interacts directly with RAD51, which is an essential protein for error-free double-strand DNA break repair by homologous recombination (Sharan et al, 1997;Wong et al, 1997;Xia et al, 2001;Pellegrini et al, 2002;Venkitaraman, 2002;Jackson, 2002;Powell et al, 2003). BRCA2 regulates both the intracellular localisation and DNA-binding ability of RAD51, and therefore loss of this control following BRCA2 inactivation may be a key event leading to genomic instability and carcinogenesis (Davies et al, 2001;Jackson, 2002;Yoshida and Miki, 2004). Whether prostate tissue is particularly susceptible to BRCA2 loss is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mutant BRCA2 is associated with Fanconi's anemia. Cell culture studies indicate that BRCA2 has several functions, including repair of double-strand breaks (DSBs) in DNA through homologous recombination, as well as regulation of transcription and the cell cycle (reviewed by Yoshida and Miki, 2004). It is hypothesized that tumor suppression by BRCA2 is related to its ability to repair DSBs through interaction with the RAD51 recombination enzyme (Shivji and Venkitaraman, 2004).…”
Section: Introductionmentioning
confidence: 99%